At the mountains' altar: anthropology of religion in an Andean community - Salomon, Frank (Routledge, 2018)
Introducing a village -- A word with the sophisticates -- The cultural voltage of researching sacred things -- About this book: ethnography and western theories of religiosity -- An alternative definition of the object: ritual studies, and Bell's fusion engine